Inhibition of lung cancer in diethylnitrosamine‐induced mice by Rhizoma paridis saponins. Issue 5 (6th March 2017) - Man, Shuli; Li, Jing; Qiu, Peiyu; Liu, Jing; Liu, Zhen; Ma, Long; Gao, Wenyuan
Abstract : Lung cancer is the foremost cause of cancer mortality and a growing economic burden worldwide. Rhizoma paridis saponins (RPS) have been reported to exhibit potential anti‐tumor effects on many kinds of tumor models. The present study was designed to investigate the mechanism‐based chemopreventive nature of RPS against DEN‐induced lung carcinogenesis in Kunming mice. As a result, the treatment with RPS reduced the severity of pulmonary histopathology. The mechanism of its antitumor effect involved in (a) reducing oxidative stress injury through up‐regulating activities of CAT and SOD; (b) down‐regulating the levels of inflammatory factors, like TNF‐α, IL6, COX‐2, and PGE2; (c) activation of caspase‐3 and up‐regulating the pro‐apoptotic protein Bax; (d) decreasing the expression of PCNA; (e) depressing the expression of cancer stem cells marker CD133; (f) suppressing aberrant expression of cytokeratin 8 and 18; and (g) inhibiting EGFR/ PI3 K/Akt, EGFR/Ras/Erk and NF‐κB pathways. Taken together, RPS would be a potent agent inhibiting lung tumor in the future.